Mode-multiplexed waveguide sensor. Issue 4 (3rd March 2016) - Ahmed, Rajib; Rifat, Ahmmed A.; Yetisen, Ali K.; Yun, Seok Hyun; Khan, Safyan; Butt, Haider
Abstract: Optical sensors enable quantification of analyte concentrations non-invasively without being affected from electromagnetic fields. The development of single-mode waveguides (WGs) is simple approach; however, limitations in the spatial distribution of the refractive index and the inability to sense multiple samples at the same time. Here, we demonstrate a multi-mode WG model and matrix inversion method (MIM) to improve spatial information in at least one dimension. This method is used to optimize and estimate three external stimulus properties in TE00, TE01 and TM00 multiplexed modes for a semi-triangular ring resonator configuration. The multi-mode WG and MIM may have applications in the development of biosensors for multi-analyte detection.